Dramatic Play in Early Childhood Education: An Interdisciplinary Reconstructionist Perspective on Cultivating Social Awareness - Winarti Agustina; Sofia Hartati; R. Sri Martini Maelani (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study investigates the role of dramatic play in early childhood education (ECE) through a Reconstructionist lens and an interdisciplinary approach. A total of 65 articles were retrieved from indexed academic databases—Google Scholar, JSTOR, ScienceDirect, and ProQuest—using keywords such as “dramatic play,” “early childhood education,” “reconstructionism,” and “interdisciplinary approach.” Of these, 30 articles were selected based on inclusion criteria including topical relevance and academic rigor, covering publications from 2013 to 2024. The research employs a Systematic Literature Review (SLR) guided by the PRISMA framework to identify, screen, and synthesize the findings. The results reveal that dramatic play contributes significantly to the development of empathy, social competence, and children's awareness of societal roles. Role-playing allows children to embody various social and professional identities, such as doctors or community leaders, while internalizing values like cooperation, justice, and responsibility. From a Reconstructionist perspective, education is seen as a means of social transformation, positioning dramatic play as a powerful tool for character development in early childhood. The interdisciplinary approach further enhances learning by integrating insights from psychology, sociology, and pedagogy. This study recommends embedding socially meaningful dramatic play into the ECE curriculum and underscores the crucial role of teachers in facilitating value-oriented role-play experiences